Procesos criminales a instancia de parte privada. Apuntes sobre su praxis en el Real Consell Criminal valenciano en época de Felipe II. - HERNÁNDEZ-FERNÁNDEZ, MARÍA-DOLORES (Scripta, 2019)
The present work explores the possibilities of knowing the valencian criminal process through the study of processes urged by individuals on the Real Consell Criminal of the Real Audiencia valenciana. The study of the justice praxis of the king in the Real Consell Criminal can provide interesting data, beyond the knowledge of the Valencian criminal process or the functioning of the justice of the Real Audiencia, also on the operation of criminal justice in the Old Order in general.